2021
DOI: 10.46234/ccdcw2021.213
|View full text |Cite
|
Sign up to set email alerts
|

Eleven COVID-19 Outbreaks with Local Transmissions Caused by the Imported SARS-CoV-2 Delta VOC — China, July–August, 2021

Abstract: Of this series of epidemics, the epidemic in Nanjing City affected the largest geographical area and had the most significant cumulative number of cases. The investigation revealed that the index case, which was China CDC Weekly Chinese Center for Disease Control and Prevention CCDC Weekly / Vol. 3 / No. 41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
1
24
0
1
Order By: Relevance
“…These patients were in the wild-type cohort. In parallel, 336 patients with COVID-19 in the delta variant cohort were admitted and hospitalized at the Third People's Hospital of Yangzhou City (TPHYC), Jiangsu Province, China, in August 2021, where the delta variant of SARS-CoV-2 has been identified as the responsible pathogen ( 21 ). No ICU patients were reported in this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…These patients were in the wild-type cohort. In parallel, 336 patients with COVID-19 in the delta variant cohort were admitted and hospitalized at the Third People's Hospital of Yangzhou City (TPHYC), Jiangsu Province, China, in August 2021, where the delta variant of SARS-CoV-2 has been identified as the responsible pathogen ( 21 ). No ICU patients were reported in this cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Since its outbreak in late 2019, coronavirus disease 2019 (COVID-19) has remained a global pandemic for nearly two years, which poses a huge test on the resilience of global public health system (1). After experiencing the large-scale epidemic in February 2020, China has entered a normalization stage of prevention and control since May 2020 (2). In response to the spread of the highly transmissible Delta variant, China adopted a new strategy called "Dynamic COVID-zero" from August 2021.…”
mentioning
confidence: 99%
“…For COVID-19 patients admitted at Yangzhou, China in August 2021 (Table 2), the epidemiological investigation confirmed that their infections were due to the spreading of delta variant SARS-CoV-2 (6). Their hematological profiles were divided into groups of patients with no, partial (one-dose), and full (two-dose) vaccinations, and then unvaccinated delta variant COVID-19 patients in Yangzhou were compared to (unvaccinated) patients in Wuhan as well as the partially or fully vaccinated patients, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…We here report a total of 677 COVID-19 patients admitted at separate centers in China, where a cohort of 341 patients was hospitalized in Wuhan, Hubei Province during January-April 2020, and a cohort of 336 patients was hospitalized in Yangzhou, Jiangsu Province on August 2021 where the infections were identified to be caused by delta variant of SARS-CoV-2 ( 6 ). Clinical characteristics centered on RBC features were elaborated and compared between two cohorts of COVID-19 patients, to distinguish its delta variant from wild-type SARS-CoV-2 in their infection profiles.…”
Section: Resultsmentioning
confidence: 99%